2020
DOI: 10.1002/cphc.201901105
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Modeling of the Surface‐Guided Self‐Assembly of Functional Molecules

Abstract: Directing the self‐assembly of organic building blocks with 2D templates has been a promising method to create molecular superstructures having unique physicochemical properties. In this work the on‐surface self‐assembly of simple ditopic functional molecules confined inside periodic nanotemplates was modeled by means of the lattice Monte Carlo simulation method. Two types of confinement, that is honeycomb porous networks and parallel grooves of controlled diameter and width were used in the calculations. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…All these circumstances stimulated us to address the formation of two ordered structures of BTB molecules, the deprotonated R phase, and the O phase which we treat both intact as well as weakly deprotonated, by using modeling methods of Monte Carlo (MC) and density functional theory (DFT). A computational approach has been instrumental recently in explaining the formation of self-organized molecular networks. The particular methodology used here was previously developed to handle the triangular- and rectangular-shaped molecules with hydrogen bonds at the vertices and employed for systems such as deprotonated TMA molecules, neutral TMA–BTB mixtures, and host–guest architectures…”
Section: Introductionmentioning
confidence: 99%
“…All these circumstances stimulated us to address the formation of two ordered structures of BTB molecules, the deprotonated R phase, and the O phase which we treat both intact as well as weakly deprotonated, by using modeling methods of Monte Carlo (MC) and density functional theory (DFT). A computational approach has been instrumental recently in explaining the formation of self-organized molecular networks. The particular methodology used here was previously developed to handle the triangular- and rectangular-shaped molecules with hydrogen bonds at the vertices and employed for systems such as deprotonated TMA molecules, neutral TMA–BTB mixtures, and host–guest architectures…”
Section: Introductionmentioning
confidence: 99%
“…The solution to the lattice gas problem in 2D as dened by eqn ( 1) is a non-trivial issue and is commonly solved by the Monte Carlo (MC) approach. 31,33,63,64 To that end, we developed an MC code to simulate coverage vs. concentration curves and to perform non-linear regression analysis of experimental data. The MC algorithm comprises several steps, where a 2D square lattice (dimensions d × d, under periodic boundary conditions) is rst generated and the occupation at each site is assigned.…”
Section: D Ising Model For Molecular Self-assembly On Surfacesmentioning
confidence: 99%
“…In parallel, mechanisms of molecular self-assembly on surfaces have been also studied using a computational, coarsegrained Monte Carlo approach. [29][30][31][32][33][34][35] These theoretical investigations examine the structural features of the 2D self-assembly for different systems ranging from simpler model tripodal molecules 31,33 to more complex chiral systems, and co-assembly in metal-organic networks. 34 In parallel to quantifying thermodynamic factors, the development of computational methods studying morphology of 2D systems is also of great importance to establish predictive power over self-assembly at the liquid/solid interface.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples of such systems are the adsorption layers of functional organic molecules [11][12][13][14]. The lattice models of organic monolayers have revealed that the phase behavior is primarily determined by the shape of the adsorbate molecule, chemical structure of the functional groups and symmetry of its arrangement in the molecule [41][42][43][44][45][46][47][48][49][50][51][52][53][54]. To form continuous organic networks on a solid surface, the functional molecules having С 2 or С 3 symmetry are typically used.…”
Section: Introductionmentioning
confidence: 99%